Reducing Blindism Behavior with Self Management Technique for Blind Students in Class VIII at SLB-A YKAB Surakarta - Dzullia, Cahaya Dwi; M, Si., Subagya; Anwar, Mohammad (Indonesian Journal of Disability Studies, 2021)
This study aims to find out the influence of self management techniques in reducing blindism behavior owned by visually impaired students in class VIII at SLB-A YKAB Surakarta. This research is a quantitative research using experimental research design with a single subject or Single Subject Research (SSR). The subjects of this study were visually impaired students of class VIII at SLB-A YKAB Surakarta. The data collection techniques that used in this study were the observation of participants and non-participants. Data analysis techniques used are visual analysis techniques in conditions and visual analysis between conditions. The results of experiments in the baseline phase were conducted as many as four sessions, obtained blindism frequency data in students as many as 20, 19, 21 and 21 times. This shows that the trend of the blindism behavior of educated participants was increased with a stability level of 100%, so that intervention was needed. The intervention phase was carried out in eight sessions and data on the frequency of blindism on students were 16, 12, 11, 11, 10, 9, 9 and 9 times. Referring to the data, it can be seen that the trend of decline and the level of stability of the data obtained was 87.5%. So that it can be concluded that self management techniques can reduce blindism behavior for visually impaired students in class VIII at SLB-A YKAB Surakarta.